(untitled) (Bangladesh Journal of Microbiology, 2019)
Currently Jute farmer faces a number of problems in jute sector such as higher labor cost, fungal diseases, low market price, natural disasters etc. As a result the production of jute is far below than the desired figure. The severe yield lost of jute depends on a number of factors of which fungal diseases play a dominant role. In the present investigation 56 samples of infected jute plants were collected from 8 (Eight) different area of Bangladesh and the samples were investigated by Agar plate and Blotter methods. Symptoms of diseases were recorded and associated fungal pathogens were purified and characterized. Based on cultural and morphological characterizations three fungal pathogens were identified as Botryodiplodia theobromae Pat. (Griffon & Maubl.), Colletotrichum corchori (Ikata and Yoshida) and Macrophomina phaseolina (Tassi) Goid and allthe isolates showed their pathogenicity on jute plants. Bangladesh J Microbiol, Volume 35 Number 1 June 2018, pp 67-73